PRECONCENTRATION OF CADMIUM (II) BY USING DOWEX 50WX-8 RESIN BASED ON FLOW INJECTION ANALYSIS - Ambarsari (NIM 105 03 026), Novita
ABSTRACT: Preconcentration technique for ion Cadmium (II) based on flow injection analysis using DOWEX 50WX-8 cation exchange resin packed on mini-coloumn with atomic absorption spectrophotometer as detector has been done. HCl solution concentration 3 M was used as an elution agent and an aqua deionization is used as an carrier. This research show the retention capacity of Dowex 50WX-8 mini-coloumn is 0,135 mg Cd (II) per gram resin. Optimum volume of Cd (II) solution which can be retained by resin is 5 mL. Optimum volume of HCl 3 M is needed to elution Cd (II) from minicoloumn is 1 mL. The precision expresses as coefficient variation for concentration 100 ppb is 3,83 %. The sensitivity and limit of detection obtain respectively 0,34 ppb and 3,41 ppb. The linier range can be attained between 5 ppb until 200 ppb; with a correlation coefficient is 0,9866. These method has a good accuracy, according to % recovery > 95 %. The study of analytical performance showed this method can be used to analysis Cd (II) on a trace concentration (ppb) in water sample. Cd (II) in water sample from Citarum river shows under limit of detection of this methode, while water sample from Saguling Lake show concentration of Cd (II) is 9 ppb and 16 ppb.